2017
DOI: 10.1111/cpr.12362
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone‐mediated angiogenic activity of endothelial progenitor cell and angiogenesis in traumatic brain injury rats were antagonized by progesterone receptor antagonist

Abstract: It may suggest that P4-mediated angiogenic activity of EPC and angiogenesis in TBI rats were antagonized by PR antagonist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
3
22
0
Order By: Relevance
“…In addition, it has been shown that the level of occludin expression in epithelial cells was inversely correlated with paracellular permeability 5355 . Moreover, administration of progesterone improved brain function through reducing BBB permeability and increasing occludin expression in rats with traumatic brain injury, and progesterone receptor antagonist directly inhibited these functions 23,56 . Braniste et al .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been shown that the level of occludin expression in epithelial cells was inversely correlated with paracellular permeability 5355 . Moreover, administration of progesterone improved brain function through reducing BBB permeability and increasing occludin expression in rats with traumatic brain injury, and progesterone receptor antagonist directly inhibited these functions 23,56 . Braniste et al .…”
Section: Discussionmentioning
confidence: 98%
“…During stroke, estrogens exert a protective action due to theirs effect on the cerebral vasculature, increasing endothelial nitric oxide synthase activity, suppressing inflammatory markers like COX-2, and reducing leukocyte adhesion (Suzuki et al, 2009 ). Similarly, in a rat model of traumatic brain injury, progesterone has been described to promote angiogenic activity of endothelial progenitor cells (Yu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, an adjunct area that can be explored is the hormone therapy in epileptic patients. To this end, convincing data indicate that endothelial cells express estrogen or progesterone receptors, and both of these hormones have been shown to protect from vascular injury/BBB dysfunction in rodent models (Si et al, 2014;Shin et al, 2016;Yu et al, 2017). Therefore, targeting the vascular hormone receptors may serve as another approach to restore BBB defects, as well as for improving the angiogenic outcome in epileptogenesis.…”
Section: Vascular Therapy For Epilepsymentioning
confidence: 99%